Chronic histological changes in deceased donor kidneys at implantation do not predict graft survival: a single‐centre retrospective analysis. (8th February 2019) - Phillips, Benedict L.; Kassimatis, Theodoros; Atalar, Kerem; Wilkinson, Hannah; Kessaris, Nicos; Simmonds, Naomi; Hilton, Rachel; Horsfield, Catherine; Callaghan, Chris J.
Summary: The use of preimplantation kidney biopsies (PIKBs) to aid deceased donor kidney utilization decisions is controversial. Outcomes of transplants that had been biopsied after the decision had been made to implant were analysed, in order to determine the association between chronic histological changes at implantation and graft outcomes. A retrospective analysis of transplants between the year range 2006–2015 was performed. Karpinski scores on biopsies were collected, and graft outcomes were analysed using univariate and multivariable techniques. Also, Karpinski scores from single and dual kidney transplants from older donors were examined to determine if knowledge of the score preoperatively would have altered utilization. Four hundred and eight single kidneys were transplanted. Although kidneys with scores >4 had lower 1‐ and 3‐year median (IQR) estimated glomerular filtration rates (eGFRs) than those scoring 0–4 (51 (37–66) vs. 35 (26–52) ml/min/1.73 m 2, P  < 0.001, and 52 (34–64) vs. 35 (24–52) ml/min/1.73 m 2, P  < 0.001, respectively), there was no significant association between Karpinski score and death‐censored graft survival on univariate or multivariable analyses. The utilization analysis (75 single and 25 dual kidney transplant recipients) suggested that systematic use of PIKBs would have resulted in 29% fewer patients being transplanted. This analysis does not support the systematic use of PIKBs to determine deceased donor kidney utilization.